1990
DOI: 10.1007/bf01314800
|View full text |Cite
|
Sign up to set email alerts
|

Benthic invertebrate larval response to substrate characteristics at settlement: Shelter preferences of the American lobsterHomarus americanus

Abstract: MarineBiology @ Springer-Verlag 1990 Benthic invertebrate larval response to substrate characteristics at settlement: shelter preferences of the American lobster H o m a r u s a m e r i c a n u s * Abstract. The factors controlling shelter selection by the first post-larval stage of the American lobster Homarus americanus were studied in the laboratory in 1988 using an experimental approach. The relative importance of shelter size, light level within shelters, number of shelter entrances, and presence of al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

1993
1993
2013
2013

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 39 publications
2
24
1
Order By: Relevance
“…Associations of small motile animals with structural refugia in benthic marine habitats can result from active microhabitat selection (Leber 1985, Herrnkind & Butler 1986, Main 1987, Boudreau et al 1990), differential mortality (Summerson & Peterson 1984, Witman 1985, Aronson 1989, or possibly dislodgement and relocation of individuals on open surfaces by waves a n d currents (Kohn & Leviten 1976). The proximate cause of the distribution of early juvenile Nucella emarginata is not known, and the ldentification of such cause was beyond the scope of this study.…”
Section: Distribution In the Fieldmentioning
confidence: 97%
“…Associations of small motile animals with structural refugia in benthic marine habitats can result from active microhabitat selection (Leber 1985, Herrnkind & Butler 1986, Main 1987, Boudreau et al 1990), differential mortality (Summerson & Peterson 1984, Witman 1985, Aronson 1989, or possibly dislodgement and relocation of individuals on open surfaces by waves a n d currents (Kohn & Leviten 1976). The proximate cause of the distribution of early juvenile Nucella emarginata is not known, and the ldentification of such cause was beyond the scope of this study.…”
Section: Distribution In the Fieldmentioning
confidence: 97%
“…Larval supply could explain local differences in settlement (Katz et al 1994, Wahle & Incze 1997. The well-known shelterseeking behavior of lobsters during settlement can dramatically improve survival during the early benthic phase (Boudreau et al 1990, Incze & Wahle 1991, Wahle & Steneck 1991, Wahle 1992, Barshaw et al 1994, Cobb & Wahle 1994 Cancer irroratus (Beninger et al 1986, Clancy & Cobb 1991, Clancy 1995. Geographical patterns in settlement (i.e.…”
Section: Several Ecological Studies On Homarus Americanusmentioning
confidence: 99%
“…Previous observations have shown that shelters of this size cannot accommodate more than 1 postlarva at one time. Since the light level within shelters is an important cue in microhabitat selection for settling lobsters (Boudreau et al 1990), this factor was manipulated to create a gradient in shelter quality. Four types of microhabitat, corresponding to shelters offering different light intensities (measured with a Biospherical quantum meter), were obtained ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…used = 480). The number of swimming, sheltered (> 3/1 body length in shelter), and benthic unsheltered postlarvae was then recorded once every 4 h during 2 d. Night counts were carried out using a red light (see Boudreau et al 1990). To avoid disturbances during the experiment, the number of sheltered postlarvae was obtained by subtracting swimming and benthic unsheltered postlarvae from the total number of individuals initially introduced to the aquarium.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation